2004
DOI: 10.1093/jn/134.2.403
|View full text |Cite
|
Sign up to set email alerts
|

The Mode of Oral Bovine Lactoferrin Administration Influences Mucosal and Systemic Immune Responses in Mice

Abstract: Food protein intake interacts with the immune system. In earlier nutritional and immunological studies, nutrients, particularly milk whey proteins, were generally administered in soluble form and by gavage. However, orogastric intubation does not represent a natural way of ingesting nutrients such as lactoferrin (Lf). We examined how different modes of oral administration of Lf could affect the regulatory effect of this molecule on intestinal and systemic immune responses. Groups of 10 female BALB/c mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 39 publications
5
54
1
1
Order By: Relevance
“…These findings suggest that fish oil increases the proportion of Th to promote acquired immunity, and that corn oil increases the proportion of CTL to improve cellular immunity of the GI tract. Several studies have indicated that CD8 T cells require CD4 T cells help for proliferation (Smith et al 2004). Combined with our results, corn oil increased the ratio of CTL, but reduced the ratio of Th.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings suggest that fish oil increases the proportion of Th to promote acquired immunity, and that corn oil increases the proportion of CTL to improve cellular immunity of the GI tract. Several studies have indicated that CD8 T cells require CD4 T cells help for proliferation (Smith et al 2004). Combined with our results, corn oil increased the ratio of CTL, but reduced the ratio of Th.…”
Section: Discussionsupporting
confidence: 88%
“…Birds' IML were isolated by a modification of the method of Davis and Parrott (1981) and Sfeir et al (2004). The middle sections of jejunum were aseptically collected immediately after slaughter at d 21, and thoroughly washed with cold calcium and magnesium ion free Hanks' balanced salt solutions (CMF).…”
Section: Isolation Of Intestinal Mucosal Lymphocytes (Iml) and Analysmentioning
confidence: 99%
“…In view of the fact that previous investigations showed that LF administration increases the numbers of some subsets of lymphocytes in the intestine (10,37), enhancement of CCR9 expression may have been due to an increase in the number of CCR9-expressing lymphocytes. It has been reported that after 1 week of oral administration of bovine LF, antigen-specific antibody and cytokine responses are induced (20). However, the effect of bovine LF observed here shortly after administration would not have been due to action as a foreign antigen.…”
Section: Discussionmentioning
confidence: 54%
“…The antibacterial activity of Lf has been well reviewed against a broad spectrum of bacterial strains [65][66][67]. Several immunological functions have been ascribed to Lf, although their detailed mechanisms remain unknown [68][69][70][71][72][73]. Lf has also been shown to inhibit tumor growth [74], fungal infections [75][76] as well as viral infections [77][78][79][80][81][82][83][84][85][86][87][88][89].…”
Section: Lactoferrinmentioning
confidence: 99%